Seeding rate and genotype effects on weeds and yield of dry-seeded rice. (June 2017) - Mahajan, G.; Kaur, G.; Chauhan, B.S.
Abstract: Weeds are the main biological constraint to wide spread adoption of dry-seeded rice (DSR). Research analyzing the effects of seeding rate on weeds and yield of DSR using newly developed genotypes adapted to DSR is not well documented in Asia. The objective of this study was to investigate the relative performance of selected genotypes in relation to seeding rate and weed infestation levels on weeds and yield of DSR in the rainy seasons of 2014 and 2015. Four selected genotypes [two cultivars (PR-115 and Dhan-202), and two recombinant inbred lines (RIL-367 and RIL-1646)], were grown in a split-split plot arrangement in a randomized complete block, with weed infestation levels (weed-free and partial weedy) in the main plots, seeding rate (100 and 200 seeds m −2 ) in the subplots, and genotypes in the sub-subplots. Total weed biomass was lower at the high seed rate (HSR; 200 seeds m −2 ) as compared to the low seeding rate (LSR; 100 seeds m −2 ), and the reduction in weed biomass varied from 40 to 72% depending on genotypes. At the LSR, the weed-competitive index (WCI) of RIL-1646 (1.13) was higher than PR-115 (0.44), but remained similar to RIL-367 and Dhan-202. At the HSR, the WCI of RIL-367 (1.57), RIL-1646 (2.24), and Dhan-202 (2.89) was higher than PR-115 (0.95). The WCI of newly developed genotypes (RIL-367, RIL-1646 and Dhan-202) increased with increased seeding rate, while for PR-115; no such increase was found. In the weed-free plots, RIL-367 at both the seeding rates had higher grain yield (5.97 t ha −1 ) than other genotypes and the lowest yield was recorded with Dhan-202, and the trend was similar at both the seeding rates. However, in the partial weedy plots, at both the seeding rates, the lowest yield was recorded for PR-115. In the partial weedy plots, the grain yield of RIL-367 was increased using the HSR. In the partial weedy plots, the plant height of RIL-367 at HSR was higher than that at LSR, and a similar trend was observed for panicle weight. There was a negative relationship between early plant height and relative grain yield loss due to weed infestation. This study indicates that the newly developed genotypes for DSR have variations in WCI, and weed control in DSR could be improved by increasing the seeding rate for these genotypes. Highlights: Use of low seed rate in DSR requires effective weed control for high yield. Pre and post herbicides are must for effective weed control in DSR. Integration of seed rates and competitive genotypes may reduce herbicides. Plasticity response of some genotypes varied with increasing seed rate.